Sex estimation techniques based on skulls in forensic anthropology: A scoping review. - Xindi Wang; Guihong Liu; Qiushuo Wu; Yazi Zheng; Feng Song; Yuan Li (PLoS ONE)
Background Sex estimation is an essential topic in the field of individual identification in forensic anthropology. Recent studies have investigated a growing range of techniques for estimating sex from human skulls. Objectives This study aims to provide a scoping review of the literature on techniques used in skull-based sex estimation, serving as a valuable reference for researchers. Sources of evidence The literature search was performed using PubMed, Scopus, and Web of Science from January 2020 to February 2024. Eligibility criteria Eligible studies have investigated issues of interest to forensic anthropology about sex estimation using skull samples. Charting methods A total of 73 studies met the inclusion criteria and were categorized and analyzed based on the anatomic sites, modalities, trait types, and models. Their accuracy in estimating sex was subsequently examined, and the results were charted. Results and conclusions Our review highlights that the 3D medical imaging technique has enhanced the efficiency and stability of skull-based sex estimation. It is anticipated that advancements in 3D imaging and computer vision techniques will facilitate further breakthroughs in this field of research.